2013
DOI: 10.2478/s11687-013-0110-x
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigation of vitellogenesis in Caryophyllaeus laticeps (Pallas, 1781) (Cestoda, Caryophyllidea, Caryophyllaeidae), monozoic tapeworm of Abramis brama (Pisces, Teleostei)

Abstract: Reinvestigation of vitellogenesis in the caryophyllidean cestode Caryophyllaeus laticeps (Pallas, 1781) has been performed using light microscope (LM) and transmission electron microscopy (TEM), and cytochemical staining with periodic acid-thiosemicarbazide-silver proteinate (PA-TSC-SP) for glycogen. Vitellogenesis is generally similar to that reported in the past, however, some new observations were made. The present study reveals the first evidence of: (i) interstitial tissue in the vitelline follicles, (ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Vitellogenesis like that described in our study has been observed in lower cestodes as follows: in gyrocotylids by Xylander (1987), amphilinids by Xylander (1988), caryophyllidids by Bruňanská et al (2012, 2013a, 2013b), bothriocephalids by Świderski and Mokhtar (1974) and Levron et al (2007), and spathebothriids by Bruňanská et al (2005) and Poddubnaya et al (2005, 2006). Common to these cestodes is a similar egg type, with a thin shell and operculated, resembling the eggs of most trematodes.…”
Section: Discussionsupporting
confidence: 83%
“…Vitellogenesis like that described in our study has been observed in lower cestodes as follows: in gyrocotylids by Xylander (1987), amphilinids by Xylander (1988), caryophyllidids by Bruňanská et al (2012, 2013a, 2013b), bothriocephalids by Świderski and Mokhtar (1974) and Levron et al (2007), and spathebothriids by Bruňanská et al (2005) and Poddubnaya et al (2005, 2006). Common to these cestodes is a similar egg type, with a thin shell and operculated, resembling the eggs of most trematodes.…”
Section: Discussionsupporting
confidence: 83%
“…The same structures were also observed in the egg-enclosing vitellocytes of the caryophyllidean cestodes W. virilis and K. sinensis and those in the vitelloduct of another caryophyllidean from freshwater teleosts, Caryophyllaeus laticeps (Pallas, 1781) [ 17 , 23 , 25 ]. The role of GER-bodies in mature vitellocytes has not been fully investigated.…”
Section: Discussionmentioning
confidence: 71%
“…General pattern of vitellogenesis of the diphyllobothriidean cestodes [7,present study] proceeds in a way commonly found in representatives of other lower bothriate eucestodes, i.e. Caryophyllidea, Spathebothriidea, Diphyllidea, and Trypanorhyncha [9][10][11][12][13][14][15][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 87%
“…Among the basal bothriate eucestodes, vitellogenesis was studied in several species of the Caryophyllidea, but with most data limited to the parasites of cyprinids in the Palearctic Region (e.g. [9][10][11]), in three species of the relictual order Spathebothriidea [12,13] from freshwater and marine teleosts, in one species of the order Diphyllidea [14] and several species of the marine order Trypanorhyncha, parasites of elasmobranchs (e.g., [15]). Therefore, the ultrastructural data on vitellogenesis are available for all but one (Haplobothriidea) orders considered representing the most basal bothriate eucestode lineages.…”
mentioning
confidence: 99%